Multiplexed femtomolar quantitation of human cytokines in a fluoropolymer microcapillary film1. Issue 16 (21st August 2015) - Castanheira, Ana P.; Barbosa, Ana I.; Edwards, Alexander D.; Reis, Nuno M.
<x xml:space="preserve">Abstract</x> Femtomolar multiplex quantitation of human cytokines using disposable fluoropolymer microfluidic strips and a multisyringe aspirator capable of performing up to 80 tests using a flatbed scanner.